Complexity in organizations : a research overview - Johannessen, Stig O. (State of the art in business research., 2022)
"Written with pace and clarity, this book is a comprehensive and compact overview and introduction to the research landscape of complexity in organizations. In addition to conveying a gripping history of how complexity has influenced organizational ideas, theories, and practices throughout the 20th century and into our present age, the book sheds light on how ground-breaking ideas in chaos and complexity research have emerged and challenged the very foundations of science into a changed vision of nature, society, and human organizations. As well as being an exciting investigation into complexity research in organizations, the book shows how, in the past, researchers who were immersed in the power politics of their day grappled with the theme of complexity in their quest to understand the dynamics of organization in nature and society. By welding fundamental theoretical themes and practical implications into the political and social contexts in which they emerged, this overview provides both depth and breadth to the history, as well as the future, of studies of complexity in organized activity. The book is a lucid and essential study of a topic that will be of interest to scholars, researchers, and students in the fields of business and management, especially those with an interest in the ways that complexity affects and transforms organizations"--